THE FACTORS AFFECT TO DECREASE OF FODDER BASE OF SERICULTURE AND THE WAYS OF DEVELOPMENT IT - KHOJIMATOV RAVSHANBEK RASULJONOVICH (IJRDO - Journal of Applied Management Science, 2020)
Mulberry is a plant that is grown for silkworm rearing. It is the exclusive food for the silkworm, which during its larval life is reared for silk production. Production of mulberry leaves in the regions is essential for organizing sericulture on sound economic lines. Besides, as a result of successful production of mulberry, it is necessary to expand constantly mulberry tree and mulberry plantations in the country. In addition, skilled labour needs in mulberry growing and silkworm rearing for high production. The article stated that essential problems and prospects of fodder base of the sericulture in Namangan region. Analyzed the current condition mulberry fodder of the Republic of Uzbekistan and the further activities of development it. Given recommendations for increasing of the fodder base in sericulture in Namangan region.